"I am allowed to be myself": A photovoice exploration of non-binary identity development and meaning-making. Issue 1 (2nd January 2021) - Cosgrove, Darren
Abstract: Social work researchers have increasingly focused on the needs of transgender communities and clients, which has resulted in the advancement of transgender-affirming practice and services; however, there has been relatively little research devoted to the experiences and needs of non-binary people. This article describes a participatory action research study that utilized photovoice methodology to understand the identity-based experiences of a group of non-binary young adult participants. Members of the group explored their individual and collective processes of coming to understand, construct and express genders that fall outside of the binary expectations they experienced on a daily basis. Findings highlight the pervasive nature of binary gender constructs and note the ways in which participant co-researchers navigate invisibility and erasure in order to reclaim their gender and build community. Implications for social work practice, policy and research are discussed.